Levinas, Latin American Thought and the Futures of Translational Ethics - Larkosh, Christopher (TTR)

(untitled) (Association canadienne de traductologie, 2004)
AbstractThis article underscores the relevance of the ethical philosophy of Emmanuel Levinas to contemporary discussions of translational ethics, especially with respect to contemplations of the discipline’s future. It posits thinking of the future as an ethical imperative against the historical backdrop of the Holocaust and other human ethical crises. Despite the foreclosure of utopian thinking that such a context might imply, there are nonetheless other modes of imagining translation in other terms, whether “dés-inter-essement,” cross-identification, or other forms of transcultural ethical consciousness. The discussion is highlighted by examples from Latin American literature, liberation philosophy and anthropology, as well as from the historical trajectory of the discipline of translation studies from the 1970’s to the present.